Pesquisa através do design e prática crítica : uma investigação sobre o desenvolvimento de artefatos críticos no processo de construção de problemas de pesquisa acadêmicos - Lorenz, Bruno Augusto (Universidade do Vale do Rio dos Sinos, 2018)
In recent years, design has also come to be regarded as an academic research approach that appropriates design practice as a means of building objects in order to achieve new knowledge - known as research through design (RtD). Taking into consideration that the process of developing an academic research work goes through a stage of identification and construction of the problem to be investigated, this dissertation discusses the impact of the development of critical artifacts in the construction of academic research problems. Critical artifacts are those created from critical practice, an RtD approach that proposes reflection through provocative strategies. A method has been developed comprising three workshops, in which eight master students explored their own research problems through the development of critical artifacts. The 25 artifacts created were analyzed using the Matrix of Common Argument Types and the Portfolio Annotations methods. Focus groups were carried out with the designers-researchers and later analyzed through the Content Analysis tool. It was concluded that (i) critical artifacts allow researchers to reach new insights about their own research themes, through Exploratory and Solving Attitudes; (ii) the practice of the critical practice can be located in three different moments of an academic research, with varied benefits; (iii) critical artifacts incorporate knowledge about the research they explore, which allows them to function as unusual means of popularizing academic knowledge. Finally, design guidelines are proposed to benefit future exercises in similar contexts.
Keywords: Pesquisa através do design; Prática crítica; Design especulativo; Design crítico; Research through design; Critical practice; Speculative design; Critical design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial